The effects of bilingualism on cognition and behaviour in individuals with attention deficits: A scoping review - Köder, Franziska; Sharma, Curtis; Cameron, Sarah; Garraffa, Maria (Frontiers in Psychology, 2022)
Background: Weaknesses in executive function have persistently been found to be associated with Attention Deficit Hyperactivity Disorder (ADHD), while bilinguals have been argued to show advantages in executive functions. While there has been some research into how bilingualism affects cognitive skills and behaviour in individuals with attention deficits, the question is still very much open. The aim of this systematic review is to gather, synthesize and evaluate existing evidence on how bilingual language experience and attention deficits affect executive function performance and ADHD-related symptoms in children and adults. Methods: Following PRISMA guidelines, a comprehensive literature search in relevant databases (PsycInfo, PubMed, Scopus, ERIC, Web of Science, EMBASE, MEDLINE, LLBA) was performed using search strings related to attention difficulties/ADHD and bilingualism. All quantitative studies were included that presented original empirical data on the combined effects of bilingualism and attention levels, regardless of age group and methodology. The screening procedure revealed nine relevant studies. Results: Across the nine identified studies a total of 2071 participants were tested. Of these, seven studies involved children and two adults. The studies varied considerably with respect to their design and methodology, the targeted executive function skills or behavioural symptoms, as well as their measure of bilingualism and attention levels. Most studies assessed aspects of executive function performance such as interference control, response inhibition, working memory or cognitive flexibility. Three studies looked at the effects of bilingualism on ADHD-related symptoms or ADHD diagnosis. Across the studies, no systematic advantage or disadvantage of bilingualism on cognitive performance or behaviour in people with attention deficits was observed. Conclusion: The limited number of identified studies provide no consistent evidence that bilingualism alleviates or intensifies attention difficulties in adults or children with ADHD. Based on the current state of research, individuals with ADHD and their families should not be concerned that learning additional languages has a negative impact on functioning or cognitive performance.